Estudo de caso em controle de formação líder-seguidor de robôs móveis: entrega de encomendas por drones - Cardoso, Emanuele dos Santos (2023)
This MSc thesis proposes a control philosophy to be applied in a package delivery task accomplished by a drone, which involves two vehicles, a terrestrial one and an aerial one. The ground vehicle would be a delivery truck, and the air vehicle would be the delivery drone that would carry out the final stage of the delivery, taking off from the truck and returning to it after completing the delivery. A control system based on the leader-follower paradigm to control a multirobot system is adopted, with a path-following controller guiding the ground vehicle and a trajectory-tracking controller guiding the delivery drone. In the delivery stage, the leader is the delivery point itself (a static leader), while when the drone should return to the truck the leader is the ground vehicle (a moving leader). In the case of the controller designed for the drone, the possibility of obstacle avoidance is included, to give the drone the ability to avoid buildings, electricity poles, and others, by contouring the obstacle from the sides. A laboratory-scale experiment is shown, whose results validate the proposed control strategy as a solution to the case study under analysis.